2013 Florida Blueberry Integrated Pest Management Guide - Jeffrey G. Williamson; Philip F. Harmon; Oscar E. Liburd; Peter Dittmar (EDIS, 2012)
Recommendations are based on information from the manufacturer’s label and performance data from research and Extension field tests. This 31-page pest management guide was adapted for Florida by Jeffrey G. Williamson, Philip F. Harmon, Oscar E. Liburd, and Peter Dittmar, from the Southeast Regional Blueberry Integrated Management Guide, and published by the UF Department of Horticultural Sciences, November 2012.